2005
DOI: 10.1111/j.0030-1299.2005.13604.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of ant attendance may induce compensatory plant growth

Abstract: S. 2005. Lack of ant attendance may induce compensatory plant growth. Á/ Oikos 111: 170 Á/178.Three levels in ant Á/plant protection systems need to be considered to fully understand how these symbiotic systems work. Here we present the effect of Oecophylla smaragdina ants on (1) the arthropod community, (2) herbivory, and (3) plant performance, within a studied mangrove ant Á/plant protection system. On Rhizophora mucronata trees in Thailand ants successfully colonised ant trees attached with a string to a na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…In the 14 comparisons of changes in the density of other predators from nine independent studies, the majority of predators studied were generalist predators, such as spiders. Some authors have argued that effects of ants on other predators tend to be less consistent than effects of ants on herbivores, with some predator taxa responding to Oecologia (2009) 160:537-549 545 ant exclusion (Sipura 2002) and others not (Karhu 1998;Gibb 2003;Offenberg et al 2005). Our results for ant effects on predators come from a relatively small number of comparisons, but they do show strong effects of ant removal on predator abundance in terrestrial communities which, in turn, have the potential to affect the composition, diversity, and abundance of the herbivore community on those plants.…”
Section: Discussionmentioning
confidence: 99%
“…In the 14 comparisons of changes in the density of other predators from nine independent studies, the majority of predators studied were generalist predators, such as spiders. Some authors have argued that effects of ants on other predators tend to be less consistent than effects of ants on herbivores, with some predator taxa responding to Oecologia (2009) 160:537-549 545 ant exclusion (Sipura 2002) and others not (Karhu 1998;Gibb 2003;Offenberg et al 2005). Our results for ant effects on predators come from a relatively small number of comparisons, but they do show strong effects of ant removal on predator abundance in terrestrial communities which, in turn, have the potential to affect the composition, diversity, and abundance of the herbivore community on those plants.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas several studies have demonstrated a negative impact of ants on the abundance of natural enemies (Eubanks, 2001;James et al, 1999;Kaplan and Eubanks, 2005;Piñol et al, 2012a) others find no effect (Chong et al, 2010;Gibb, 2003;Offenberg et al, 2005) or even find positive effects of ants on the community of natural enemies (Peng and Christian, 2013;Stewart-Jones et al, 2007). The same or even greater variability is reported at the species level; natural enemies, even species belonging to the same taxonomic order, may be affected differently by ants.…”
Section: References Therein)mentioning
confidence: 95%
“…For each leaf, we visually estimated the proportion of leaf area lost due to herbivores to the presumed total leaf area to the nearest one fourth increment (25%) of proportion, referring to the methods in previous studies (Offenberg et al 2005;Eichhorn et al 2006). When we found a leaf loss, we estimated the total leaf area of the leaf at the time before leaf loss by referring to the total leaf area of neighboring non-damaged leaves.…”
Section: Methodsmentioning
confidence: 99%